Pengaruh Model Pembelajaran STAD Menggunakan Media Powerpoint untuk Meningkatkan Motivasi Belajar IPAS Siswa Kelas IV SD Negeri Sidorejo Lor 01 Kota Salatiga Semester II Tahun Ajaran 2022/2023 - Rimon Hilkia Kafiar; Krisma Widi Wardani (Journal on Education, 2023)
This study aims to determine whether there is an effect of the Student Teams Achievement Division (STAD) learning model using PowerPoint media to increase motivation to learn Natural and Social Sciences (IPAS) for fourth grade students of SD Sidorejo Lor 01 Elementary School, Salatiga City. The variables in this study are the independent and dependent variables. This research is a quantitative study using the True-Experimental method with Pretest-Posttest Control Group Design. The subjects of this study were students of class IVa and class IVb of Sidorejo Lor 01 Public Elementary School, Salatiga City. The data collection technique was in the form of distributing questionnaires to students in grades IVa and IVb of elementary schools. The hypothesis testing data analysis technique was carried out to find out whether there was or was not the influence of the Student Teams Achievement Division (STAD) Learning Model (X1), using Powerpoint Media (X2) to partially increase learning motivation (Y). The data used hypothesis t test is used to determine the significance of the effect of the independent variable partially or on the dependent variable Based on the results of the t test it is known that sig 0.195 < 0.2759 then Ho is accepted and Ha is rejected or sig 0.180 > 0.05 then it has no effect on Variable X1 (STAD model) uses X2 (Media PowerPoint), on Y (Learning Motivation) Science Science Elementary School Students Sidorejo Lor 01 Salatiga.So it can be concluded that there is no effect of the student teams achievement division (STAD) model using powerpoint media on increasing motivation learn science science for fourth graders of Sidorejo Lor 01 Public Elementary School, Salatiga City.